Estudo da qualidade física e química das águas subterrâneas da área urbana de Sinop/MT - Knechtel, Régis (2015)
Groundwater has become an increasingly exploited resource worldwide, and Sinop-MT is no exception. With public and private supply exclusively underground, the city can be considered as a high vulnerability site to contamination due to its location on the Parecis Group aquifers, which has a high hydraulic conductivity and water table very close to the surface. In this context, the main objective of this work is to study the groundwater quality of Sinop-MT urban area by determining their physical and chemical parameters, in order to support the conservation of this resource and to enable the validation of vulnerability maps in forthcoming studies. Due to its essentially quartz-feldspar composition, the Parecis Group groundwaters have low concentration of all the analyzed ions, low salinity, pH trending to acidic and low alkalinity. A possible contamination was also detected in one of the city wells, which may be caused by constructive problems. Nevertheless, the waters have good physical and chemical quality and, with the adequacy of domestic and industrial waste dumps of the city and greater control over the use of pesticides, it is possible to ensure the conservation of the Parecis Aquifer System.